TI_GERICHTE 90.2015.108 vom 25. Oktober 2017 , Revisione di un piano regolatore - limite forestale e urbanizzazione - TI Tribunale d'appello (2017)
Revisione di un piano regolatore - limite forestale e urbanizzazione